Volatile Compounds and Chemical Profiles in Unroasted Coffee: Impact of Lactic Acid Bacteria Species and Dose for On-farm Processing - Trisnawati, Ni Wayan; Aurum, Fawzan Sigma; Nurhantoro, Irsan; Wibowo, Nendyo Adhi (Indonesian Food Science and Technology Journal, 2026)
While post-harvest fermentation is known to influence coffee quality, the specific impact of lactic acid bacteria (LAB) starter cultures on modulating the volatile aroma precursor diversity in unroasted green coffee beans remains underexplored. This knowledge gap limits the industry's ability to move beyond spontaneous fermentation to predictably target specific aroma profiles. This study investigated the species- and dose-dependent effects of locally cultured Leuconostoc pseudomesenteroides and Pediococcus pentosaceus (1.5–6% w/v inoculum) on the green bean's chemical profile. The unroasted beans were analyzed using HS-SPME-GC–MS for volatile aroma precursors alongside caffeine and proximate composition. The chemical profile diverged significantly following LAB inoculation, with volatile diversity increasing by 32–45% relative to the control. The two species demonstrated divergent impacts: L. pseudomesenteroides (3–4.5% inoculum) drove significant proteolysis (protein content decreased from a mean of 11.8% to 8.5%) and was associated with a ~47% increase in measured caffeine, enriching precursors for floral (2-phenethyl acetate) and buttery (2,3-pentanedione) notes. Conversely, P. pentosaceus  produced nutty precursors (e.g., methylpyrazine) while preserving the bean's protein and fat matrix. These findings provide a clear biochemical roadmap for the coffee industry. They demonstrate that targeted LAB inoculation is a viable strategy to predictably engineer green bean chemistry, allowing producers to deterministically steer the final cup profile toward either complex floral notes or classic, matrix-preserved nutty characteristics.